2008
DOI: 10.1103/physrevd.78.063006
|View full text |Cite
|
Sign up to set email alerts
|

Shear viscosity in neutron star cores

Abstract: We calculate the shear viscosity η ≈ ηeµ +ηn in a neutron star core composed of nucleons, electrons and muons (ηeµ being the electron-muon viscosity, mediated by collisions of electrons and muons with charged particles, and ηn the neutron viscosity, mediated by neutron-neutron and neutronproton collisions). Deriving ηeµ, we take into account the Landau damping in collisions of electrons and muons with charged particles via the exchange of transverse plasmons. It lowers ηeµ and leads to the non-standard tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
264
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(269 citation statements)
references
References 36 publications
3
264
2
Order By: Relevance
“…Therefore, in the analysis of the r-mode instability in nonsuperfluid stars, it has been usual to take η = η n , using for η n the one calculated by Flowers and Itoth [86,87], and fitted by Cutler and Lindblom [88] in the simple form where ρ 15 and T 9 mean that the density and temperature are given in units of 10 15 g cm −3 and 10 9 K, respectively. Nevertheless, recently, Shternin and Yakovlev [89] have shown that the main contribution to the shear viscosity at the temperatures relevant for the spin-down evolution of neutron stars comes from electron scattering when Landau damping is taken into account in the collision of charged particles mediated by the exchange of transverse plasmons. This electron contribution can be written as [18,89] η e = 4 × 10…”
Section: Bulk and Shear Viscositiesmentioning
confidence: 99%
“…Therefore, in the analysis of the r-mode instability in nonsuperfluid stars, it has been usual to take η = η n , using for η n the one calculated by Flowers and Itoth [86,87], and fitted by Cutler and Lindblom [88] in the simple form where ρ 15 and T 9 mean that the density and temperature are given in units of 10 15 g cm −3 and 10 9 K, respectively. Nevertheless, recently, Shternin and Yakovlev [89] have shown that the main contribution to the shear viscosity at the temperatures relevant for the spin-down evolution of neutron stars comes from electron scattering when Landau damping is taken into account in the collision of charged particles mediated by the exchange of transverse plasmons. This electron contribution can be written as [18,89] η e = 4 × 10…”
Section: Bulk and Shear Viscositiesmentioning
confidence: 99%
“…This result is valid over the density range 10 14 < ρ < 4 × 10 14 . More recent calculations for the electron viscosity have been performed by Andersson et al (2005) and Shternin & Yakovlev (2008) accounting for superfluidity of proton matter. The former finds results broadly consistent with Equation (53), while the latter accounts for transverse Landau damping in charged particle collisions neglected in previous studies, an effect that results in viscosities a factor of three smaller than that predicted by Equation (53).…”
Section: Application To Neutron Starsmentioning
confidence: 99%
“…Due to the multi-fluid nature of the superfluid/superconducting mixture, there are not simply two components coupled by a single resistive force. We could imagine a variety of ways for the components to interact with each other ranging from electron scattering (Sauls, Stein & Serene 1982;Alpar, Langer & Sauls 1984;Andersson, Sidery & Comer 2006) and vortexfluxtube interactions (Ruderman, Zhu & Chen 1998;Jahan-Miri 2000;Link 2003) to shear or bulk viscosity (Andersson, Comer & Glampedakis 2005;Shternin & Yakovlev 2008;Manuel, Tarrus & Tolos 2013). Choosing a more pedagogical approach to our problem, we pick one specific mechanism, determine how it affects the electrons on mesoscopic scales and translate this into a macroscopic picture.…”
Section: The Coupling Force: 'Standard' Resistivitymentioning
confidence: 99%